Recent advances in hepatitis B virus research: A German point of view - Glebe, Dieter (Baishideng Publishing Group Co., Limited, 2007)
More than 30 years after the discovery of human hepatitis B virus (HBV) this virus remains to be one of the major global health problems. In infected adolescents or adults, 5%-10% will lead to a chronic carrier state, whereas in infected neonates up to 90% develop chronicity. It is estimated that about 370 million people are chronic carriers of HBV worldwide. In many regions of the world, chronic HBV infection is still the major cause of liver cirrhosis and hepatocellular carcinoma. During the last 30 years, many steps of the viral life cycle have been unravelled, mainly due to cloning, sequencing and expression of the genomic DNA extracted from HBV virions. This has lead to the development of a safe and efficient vaccine and sensitive tests for HBV surface protein (HBsAg) allowing reliable diagnosis and screening of blood products. More recently, a growing number of reverse transcriptase inhibitors have been developed. However, together with these improvements new deficiencies in prevention and cure of HBV infections are becoming apparent. Although HBV is a DNA virus, it is highly variable under immunity or drug induced selection pressure, resulting in vaccine-related escape mutants and drug resistance. To overcome these challenging problems new antivirals and optimised vaccines have to be developed.